(3cJGH KGhKhSjhS aj GdCjGe hGddjGdis - (3KGhPhSjhSs
(3ChdgG (B:s
(3GdTeS JJMQc MQcI eYJOdI VO MQcI Gdcd Ydi efWbI GdHQhL hjSei GdOGFQI GdTeSjI s
(3BNQgG (B:s
(3GPG fbUJ cd SfI bhSkG eKd M hGLJeYJ efgG bSei Ydi GVYGa M g Je GdcJGH HYhf Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B66 (3ef faS GdHYKIs
(3HgG CTcGd gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1401s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs